Physical, chemical and phytochemical assessment of Physalis fruits over the harvest period Avaliação física, química e fitoquímica de frutos de Physalis, ao longo do período de colheita - Lima C.S.M. (2012)
Physalis peruviana L. is a species that has been introduced in small fruit plantations. It is treated as an annual crop, and its main method of propagation is by seed. Its cultivation presents differentiated harvest dynamics, with a harvesting period duration exceeding three months. It is believed that due to the long harvest associated with different sowing seasons, there may be variations in the fruit characteristics. The aim of this study was to assess the physical, chemical and phytochemical characteristics of Physalis peruviana fruits during the harvest period, according to two sowing seasons. The experiment was carried out in 2007/2008. The seeding was performed at two different times (09/04/2007 and 11/26/2007) and transplantation was performed when fruits were at the second true leaf stage. The fruits were harvested at 120, 150, 180, 210 and 240 days after transplantation and assessed for total mass and skin color, as well as their soluble solids (SS) content, titratable acidity (TA), phenols and total carotenoids, and also the SS/TA ratio and antioxidant activity. The Physalis fruits present physical, chemical and phytochemical variations through the harvest period for the two sowing seasons. The plant development, after transplantation, led to an increase in mass, soluble solids, phenols and carotenoids as well as the SS/TA ratio. In color and antioxidant activity, the highest values were obtained with the first harvest (120 days). The September sowing provided better quality of fruits.